Os limites da democracia participativa na Constituição Federal de 1988 a partir da Ação Direta de Inconstitucionalidade n° 244-9 do Rio de Janeiro - Aguiar, Carlos Eduardo Ferreira (2023)
The history of fundamental rights has seen moments of tension over time, but the Bourgeois Revolutions changed the paradigm, placing individuals at the center of society and the state. This led to the recognition of human individualities and the limitation of state power, resulting in the promulgation of fundamental rights that ensure a dignified life. However, it is important to understand that rights are shaped by historical and geographical context, reflecting the values of a society influenced by various interests. While the Bourgeois Revolutions focused on the individual, subsequent proletarian revolutions focused on social issues and industrial needs. Today, we face new challenges where peace is no longer a distant promise but an urgent necessity for human survival. This makes the study of democracy crucial, both globally and in the Brazilian context. This study focuses on participatory democracy, with an emphasis on the Brazilian state, and seeks to answer the question: "What are the material limits of participatory democracy in the 1988 Federal Constitution?" To answer this question, we explored global and national history, as well as sociological aspects related to the formation of the state and Brazilian political culture. All of this culminated in the 1988 Constitution, which reintegrated Brazil into a democratic regime, creating a representative democracy with elements of popular participation. For the legal analysis, we used the Direct Action of Unconstitutionality No. 244-9 of Rio de Janeiro. During the judgment of ADI 244-9/RJ, the Supreme Federal Court reaffirmed the principles established by the Constitution, and Minister Sepúlveda Pertence addressed criticisms of sporadic instruments of Brazilian participatory democracy, as well as pointing out the possibilities of popular participation outlined in the Constitution. The study adopted a qualitative approach in law, using methods of theoretical-bibliographical, documentary, and jurisprudential data collection and analysis. This work is exploratory, descriptive, and purely academic in nature. Thus, it is highlighted that the current legal reality is the result of the historical journey of Brazilian society and the global formation. Therefore, it is crucial to understand fundamental rights as an intrinsic part of society and to use participatory mechanisms in the Constitution to combat political apathy and strengthen democracy as a whole.